Mechanism of Cepharanthine Cytotoxicity in Human Ovarian Cancer Cells - Payon, Vilawan; Kongsaden, Chanaporn; Ketchart, Wannarasmi; Mutirangura, Apiwat; Wonganan, Piyanuch (Planta Medica, 2019)
Cepharanthine (CEP), a medicinal product derived from Stephania cephalantha Hayata, possesses a potent cytotoxicity against several types of cancers. Recently, we have found that CEP could efficiently inhibit the growth of mutated p53 colon cancer cells, which are often resistant to commonly used chemotherapeutic agents. In this study, we evaluated the cytotoxic effect and the underlying mechanisms of CEP on both chemosensitive CaOV-3 and chemoresistant OVCAR-3 ovarian cancer cell lines. The present study demonstrated that CEP significantly inhibited the growth of CaOV-3 and OVCAR-3 cells in a time- and concentration-dependent manner. CEP arrested CaOV-3 and OVCAR-3 cells in the G1 phase and S phase of cell cycle, respectively. Western blot analysis demonstrated that CEP markedly increased the expression of p21Waf1 protein and decreased the expression of cyclins A and D proteins in both CaOV-3 and OVCAR-3 cells. Additionally, CEP triggered apoptotic cell death in OVCAR-3 cells. Taken together, the above results suggest that CEP is a promising anticancer drug for ovarian cancer.
Keywords: cepharanthine; Stephania cephalantha; Menispermaceae; cytotoxicity; ovarian cancer; cell cycle arrest; apoptosis